The new income tax to the fair "CREE" and scope in finance from the state (2013)
"CREE" new tax on tax reform 2012 seeking equity, the idea lower imporrenta 25%, create CREE 8% improving profits and governmental collection, 2014 will raise $ 51 billion, down 8.7 trillion, CREE increases by $ 10.1 billion, increases $ 1.4 trillion, para-down to 16%, 13.5% corresponds to Sena, ICBF and Health CREE as contributing companies and legal persons but excludes some, natural persons benefited are not canceled contributions and no canceled CREE, CREE the destination is direct to Sena, ICBF and Health, but the years 2013, 2014 and 2015 to support higher education institutions and social investment, a higher collection guaranteed by the government completed if there is not expected, companies finally raised their income tax and labor intensive more, continue to assess taxation to enhance their impact.